Executive remuneration and organizational life cycles: a focus on Brazilian companies - Oliveira, Alan Santos; Almeida, Karla Katiuscia Nóbrega; Lucena, Wenner Glaucio Lopes (Revista de Administração da UFSM, 2019)
This study aimed to analyze the remuneration of executives in each phase of the business life cycle. A descriptive, documentary, survey-type study was performed with a predominantly quantitative approach, using a sample of 560 observations across 112 companies. For the definition of the current life cycle phase of each company analyzed, Dickinson’s (2011) methodology was chosen, which classifies the life cycle into the five phases of start-up, growth, maturity, turbulence, and decline, based simultaneously on the signs of the operating, investment, and financing cash flows. The construction of the econometric model was based on Madhani (2012), Ventura (2013), and Koh et al. (2015). The results suggest that the highest level of executive compensation was in the turbulence phase, followed by the growth, decline, and start-up phases, with the lowest level observed in the maturity phase. It was concluded that the level of remuneration paid to the executives of the companies studied herein is related to the organizational life cycle, which corroborates the contingency and agency theories.